Setting up a delivery service for Shapadu Air Freight / Khairul Effendy Abu Bakar - Abu Bakar, Khairul Effendy (1993)
This study was designed to assess the degree to which Shapadu Air Freight needed to operate its own delivery services. It was based upon the problems that was faced by hiring private vehicles for the movement of customers' goods. In addition, this study was designed to determine the appropriate vehicle fleet to serve the current need of Shapadu Air Freight, to formulate the initial capital investment that would be needed and the propose whether such a decision was viable or not.